Analysis of competition in the life sciences industry and strategies to lead in high growth markets - Suchoňová, Katarína (2022)
This thesis aims to conduct a strategic analysis of the company Thermo Fisher Scientific. The theoretical background described the tools and frameworks commonly used for strategic analysis. Moreover, the methodological tools used for the practical part are explained. Within the practical part, the analysis consists of the analysis of the entire business environment of the company. The thesis includes the analysis of the external environment with using the PEST analysis, but also the microenvironment with the Porters Five Forces analysis. Furthermore, the analysis of the competitors is conducted. The internal analysis focuses on finding strengths and weaknesses of the company. Overall, the findings of this analysis are summarized though a SWOT framework. The SWOT analysis is followed by the recommendations of strategic decisions the company should take with suggested implementations.